A latent variable modelling approach for the pooled analysis of individual participant data on the association between depression and chlamydia infection in adolescence and young adulthood in the UK. (3rd July 2018) - Koukounari, Artemis; Copas, Andrew J.; Pickles, Andrew
Abstract: Despite the increasing evidence of association between chlamydia infection and depression, currently there is a paucity of research with limited scope to understand better the temporal nature of the relationship between them. We consider this problem in adolescence and young adulthood by pooled analysis of 7250 participants from the Avon Longitudinal Study of Parents and Children and the third National Survey of Sexual Attitudes and Lifestyles. We propose a latent variable modelling approach which can handle harmonization of categorical variables including ordinal measures from the two studies as well as measurement error and time trends.